FUNCTIONS OF REBORROWED WORDS (E Global Congress, 2023)
The thesis is dedicated to the functions of reborrowings and their peculiarities in communication. It is clear that languages evolve over the centuries and words undergo changes. Initially, we have tried to elaborate reborrowings and their functions in this thesis.